Оцінка перспектив застосування БПЛА для внесення засобів захисту рослин в задачах прецизійного землеробства - Зацерковний, В.; Ворох, В.; Zatserkovnyi, V.; Vorokh, V. (Видавництво Львівської політехніки, 2025)
Останніми роками світове аграрне співтовариство все більше використовує технології прецизійного земле- робства, щоб досягти оптимальної продуктивності кожного поля, зменшити витрати, забезпечити екологічну стійкість та захист природного середовища. Сучасні безпілотні літальні апарати (БПЛА) надають актуальну ін- формацію про стан і динаміку зростання посівів, чагарників та дерев, за їх допомогою виконують захисне оброб- лення полів і багаторічних насаджень пестицидами. Сучасні БПЛА оснащені мультиспектральними камерами, висока якість зображення яких дає змогу точно діа- гностувати проблемні ділянки сільськогосподарських угідь, а також обладнані засобами для внесення хімікатів. Переваги використання БПЛА для внесення пестицидів – висока точність, уникнення пошкодження сільськогос- подарських культур, відсутність ущільнення ґрунтів, зменшення витрат на захист рослин тощо. БПЛА викону- ють обприскування за попередньо визначеним маршрутом, уникаючи появи смуг перекриття і не залишаючи необроблених ділянок, як тракторні обприскувачі, не обладнані системою GPS.

The rapid population growth of our planet in recent decades necessitates increased food production. However, the extensive method of increasing food production by expanding arable land is not realistically feasible. The lack or incompleteness of knowledge about soil and crop conditions, weather patterns, improper or incomplete utilization of the potential of plant protection products (PPPs), irrigation issues, errors in yield forecasting, and insufficient information on market trends contribute to losses and additional costs for farmers. The use of precision agriculture technologies helps address these and many other challenges. In recent years, the global agricultural community has increasingly adopted precision agriculture technologies, enabling optimal productivity from every field, reduced costs, ecological sustainability, and environmental protection. Modern unmanned aerial vehicles (UAVs) not only provide up-to-date information on the condition and growth dynamics of crops, shrubs, and trees but also perform protective treatment of fields and perennial plantations with pesticides. Contemporary UAVs are equipped with multispectral cameras whose high-quality imaging allows for precise identification of problematic areas in agricultural lands. Additionally, these UAVs are outfitted with systems for chemical application. One of the pressing issues in modern agriculture is reducing the use of pesticides and biopreparations while simultaneously increasing their effectiveness. The advantage of using UAVs for pesticide application lies in their high precision, avoidance of crop damage, prevention of soil compaction, reduced plant protection costs, and more. UAVs perform spraying along pre-determined routes, avoiding overlap strips and untreated areas, as is often the case with tractor sprayers not equipped with GPS systems.
Assessment of prospects for using UAVs for plant protection product application in precision agriculture tasks
Keywords: прецизійне землеробство; моніторинг; цифрове сільське господарство; дистанційне зонду- вання; засоби захисту рослин (ЗЗР); пестициди; БПЛА; підвищення врожайності; рентабельність та ефективність сільського господарства; precision agriculture; monitoring; digital farming; remote sensing; plant protection products (PPPs); pesticides; UAVs; yield improvement; profitability; and agricultural efficiency; 528